Tunneling Nanotubes: Intimate Communication between Myeloid Cells - Dupont, Maeva; Souriant, Shanti; Lugo-Villarino, Geanncarlo; Maridonneau-Parini, Isabelle; Vérollet, Christel (Frontiers in Immunology, 2018)
Tunneling nanotubes (TNT) are dynamic connections between cells, which represent a novel route for cell-to-cell communication. A growing body of evidence points TNT towards a role for intercellular exchanges of signals, molecules, organelles and pathogens, involving them in a diverse array of functions. TNT form among several cell types, including neuronal cells, epithelial cells and almost all immune cells. In myeloid cells (e.g., macrophages, dendritic cells and osteoclasts), intercellular communication via TNT contributes to their differentiation and immune functions. Importantly, TNT enable myeloid cells to communicate with a targeted neighboring or distant cell, as well as with other cell types, therefore creating a complex variety of cellular exchanges. TNT also contribute to pathogen spreading as they serve as “corridors” from a cell to another. Herein, we addressed the complexity of the definition and in vitro characterization of TNT in innate immune cells, the different processes involved in their formation, and their relevance in vivo. We also assess our current understanding of how TNT participate in immune surveillance and the spread of pathogens, with a particular interest for HIV-1. Overall, despite recent progress in this growing research field, we highlight that further investigation is needed to better unveil the role of TNT in both physiological and pathological conditions.